Identity of the People from Boyacá, Carranguera Music (2020)
The objective of this research article is to explain the identity features of the people from Boyaca, such as typical dress, dialect, regional products, and some customs,  from a sociolinguistic analysis of the lyrics of the representative songs of Jorge Velosa. In this paper, the song “I am also Boyaco[1]” is taken as a specific case study. Initially, the relationship between language, culture, and identity is succinctly presented; later the generalities of carranguera music and its main exhibitor Jorge Velosa are exhibited; it concludes with a partial analysis of a sociophonetic, sociogrammatical, sociolexical and sociocultural type of the studied song.   [1] “Boyaco” is the abbreviated demonym for people from Boyaca.